Choristoderes and the freshwater assemblages of Laurasia - Matsumoto, R.; Evans, S. E. (Journal of Iberian Geology, 2010)
Choristoderes are freshwater aquatic diapsid reptiles of uncertain phylogenetic position. Although the lineage probably diverged from other diapsids in the Permo Triassic, choristoderes apparently never reached Gondwana. Within Laurasia, however, they have been recovered from Japan, China, Mongolia, Trans-Baikal Russia, Central Asia, Western Europe, and North America, reaching extreme northern latitudes. Setting aside controversial Triassic records, their known temporal range currently extends from the Middle Jurassic (Britain, Kyrgyzstan) to the Miocene (Czech Republic). However, although small choristoderes are known to span the entirety of this period, the larger, more derived neochoristoderes are recorded only from the Early Cretaceous through to the earliest Eocene. The gavial-like neochoristodere Champsosaurus is the most familiar taxon, characterised by large size, a long rostrum and flared temporal fenestrae, but research over the last three decades has revealed many new genera and exposed an unexpected diversity in terms of body size (small to relatively large), neck length (long v. short) and skull morphology (longirostrine v. brevirostrine, open v. closed lower temporal fenestrae). Typically choristoderes occur as part of a mesic assemblage that includes fish, lizards, mammals, turtles, frogs, salamanders, small dinosaurs and, usually, crocodiles. At maturity, Jurassic choristoderes were generally smaller than co-occuring crocodiles and were relatively unspecialized postcranially. The Early Cretaceous of Asia saw a dramatic diversification of choristoderes, including the appearance of much larger neochoristoderes. Perhaps significantly, the relevant Asian horizons (e.g. Yixian Formation, China; Okurodani and Kuwajima formations, Japan) yield no crocodiles. In Late Cretaceous and Paleogene horizons however, across Euramerica, large gavial-like neochoristoderes came to share freshwater ecosystems with a diversity of crocodiles, the neochoristoderes apparently occupying a specialist (gavial-like) piscivorous niche as long as it was available and resources were adequate.